Evaluation of Prognostic Factors in Early-Stage Endometrial Cancer - Khanom, Afroza; Begum, Shirin Akter; Amatullah, Mehriban; Mahmud, Tasfia; Zahan, Naznin Akter; Akter, Nasrin (Archives of Clinical and Biomedical Research, 2024)
Background: Endometrial cancer (EC) is the most common malignancy of the female genital tract and the fourth most common gynecological cancer. Prognostic factors of endometrial carcinoma remain uncertain. This study aims to evaluate the prognostic factors in patients with early stage endometrial cancer. Methods: This cohort study was conducted at the Department of Gynaecological Oncology, NICRH, from July 2016 to August 2017. A total 30 patients with endometrial cancer having history of total abdominal hysterectomy and bilateral salpingo-oophorectomy with lymphadenectomy were included in this study. Results: Among 30 patients the highest 11(36.7%) each belonged to age group 41-50 and 51-60 years with a mean age of 47.75±6.13. BMI revealed that 25(83.3%) patients had BMI ≥25 and rest 5(16.7%) had BMI 18.5-24.9. The highest number of 28(93.3%) patients had tumor size <4cm whereas only 2(6.7%) patients had tumor size ≥4cm. The mean tumor size was 2.2±0.67 cm. 21(70%) had endometroid carcinoma and only 9(30%) had nonendometroid carcinoma. It was observed that 14(46.7%), 11(36.7%) and 5(16.7%) had Grade I, II and III endometrial carcinoma respectively. 20(66.7%) had myometrial invasion, 2(6.7%) had LVSI and 11(36.7%) had pelvic lymph node metastasis. 23(76.67%) and 7(23.33%) received EBRT and no EBRT respectively as adjuvant treatment. After treatment including surgery 27(90%) patients were survived with no locoregional recurrence and metastasis. Prognostic factors included Histology type, lymph node metastasis, LVSI and adjuvant radiotherapy (P = < 0.05). Conclusion: Staging itself, lymph node metastasis, presence of LVSI are the most significant factors in case of endometrial carcinoma.